Analisis Pelayanan Kartu Tanda Penduduk Elektronik untuk Meningkatkan Validitas Data Kependudukan - Maksum Syahri Lubis (Universitas Negeri Medan, 2018)
Government is an organization that protects and serves the entire community in its territory. Thus, service and accountability are worth giving for the welfare of society. The Electronic Population Identity Card (E-KTP) program that is being run has encountered many problems including the process of recording data that has not touched all levels of society and its printing for those who have been recorded constrained because the blanks have run out and have not received supplies from the central government. This study is a descriptive study that uses qualitative methods with normative sociological and empirical juridical approaches. The results of the discussion stated that indeed data recording carried out by the government to date does not reflect the reality in the field. Thus, the government is required to do a data re-tape and provide E-KTP blanks according to regional government data promptly.